Response of the ultra high performance concrete under dynamic compressive loading - Nela Krčmářová; Jan Falta; Tomáš Fíla; David Čítek (Acta Polytechnica CTU Proceedings, 2023)
Ultra high performance concrete is a modern cementitious material which exhibits excellent mechanical properties such as damage tolerance, fracture toughness and durability. These features make this materials suitable for wide range of applications where is the material subjected to different modes of loading and different loading rates. This paper deals with measurement of the Ultra high performance concrete reinforced with steel fibres in quasi-static compression mode of deformation and two elevated strain rates using split Hopkinson pressure bar. The results of the measurement show high increase of the mechanical properties with elevated strain rate.